2020
DOI: 10.1007/s11126-020-09827-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with experienced stigma among people diagnosed with mental ill-health: a cross-sectional study

Abstract: Purpose: to examine the relationship between religiosity, social support, trauma, quality of life and experienced stigma of mental illness amongst a population diagnosed with mental ill-health. Methods: A cross-sectional survey of day service users in Northern Ireland (n = 295) covering a range of issues including religiosity, social support, quality of life and prior experience of trauma. Stigma was measured using a recognised stigma scale. We used multinomial logistic regression to examine risk factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
6
9
0
Order By: Relevance
“…Another study in Liberia among Ebola virus disease survivors found that older adults were at a lower risk of stigma than those aged 20–49 years ( Kelly et al, 2019 ). Similar findings have also been reported in other studies investigating the level of stigma among patients with mental health illnesses ( Nugent et al, 2021 ; Mackenzie et al, 2019 ). One possible explanation for the lower prevalence of stigma among older adults is that they are more skilled at emotion regulation in stressful situations than young adults ( Knight et al, 2007 ; Urry & Gross, 2010 ; Abuhammad, Alzoubi & Khabour, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Another study in Liberia among Ebola virus disease survivors found that older adults were at a lower risk of stigma than those aged 20–49 years ( Kelly et al, 2019 ). Similar findings have also been reported in other studies investigating the level of stigma among patients with mental health illnesses ( Nugent et al, 2021 ; Mackenzie et al, 2019 ). One possible explanation for the lower prevalence of stigma among older adults is that they are more skilled at emotion regulation in stressful situations than young adults ( Knight et al, 2007 ; Urry & Gross, 2010 ; Abuhammad, Alzoubi & Khabour, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, further research is needed to elucidate the specific mechanisms underlying this relationship. Notably, other recent research suggests that younger people with mental illness report more mental illness stigma ( Bhavsar et al, 2019 ; Nugent et al, 2020 ). In the present study, however, age was associated with acceptability of home treatment independently of the influence of social distance or other factors related to stigma-related mental illness knowledge.…”
Section: Discussionmentioning
confidence: 96%
“…[ 5 ] We also found that SUD patients with higher perceived social support were less likely to perceived stigma, which is consistent with earlier studies of Birtel et al .,[ 29 ] Akdağ et al .,[ 30 ] and Nugent et al . [ 31 ] who showed that perceived social support is negatively associated with perceived stigma. A possible explanation is that SUD patients with high levels of social support are able to utilize their supports in a way that allows for effective coping with stigma and its negative consequences, i.e., patients who perceived close others (e.g., family or friends) to be supportive may help decrease the society's negative evaluation and help them develop a more positive sense of self, leading to less perceived stigma.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that SUD patients with high levels of social support are able to utilize their supports in a way that allows for effective coping with stigma and its negative consequences, i.e., patients who perceived close others (e.g., family or friends) to be supportive may help decrease the society's negative evaluation and help them develop a more positive sense of self, leading to less perceived stigma. [ 29 31 ] Meanwhile, people with SUDs often experience more socially excluded, less social interaction, and withdraw from their support network (e.g., family, friends, or significant others). As a result, they may be perceived discrimination and lose social support as an important coping strategy, which can lead to increases perceived stigma of addiction.…”
Section: Discussionmentioning
confidence: 99%